2016
DOI: 10.1016/j.expneurol.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal measures of cognition in the Ts65Dn mouse: Refining windows and defining modalities for therapeutic intervention in Down syndrome

Abstract: Mouse models have provided insights into adult changes in learning and memory in Down syndrome, but an in-depth assessment of how these abnormalities develop over time has never been conducted. To address this shortcoming, we conducted a longitudinal behavioral study from birth until late adulthood in the Ts65Dn mouse model to measure the emergence and continuity of learning and memory deficits in individuals with a broad array of tests. Our results demonstrate for the first time that the pace at which neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
52
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 80 publications
10
52
2
Order By: Relevance
“…Our data are congruent with previous studies that have demonstrated delay in the acquisition of developmental milestones during the early postnatal period in Ts65Dn mice1821141. Like DS infants, the Ts65Dn mice ultimately achieve developmental milestones but with significant delay as compared to their WT littermates.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data are congruent with previous studies that have demonstrated delay in the acquisition of developmental milestones during the early postnatal period in Ts65Dn mice1821141. Like DS infants, the Ts65Dn mice ultimately achieve developmental milestones but with significant delay as compared to their WT littermates.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study reported a relationship between early motor skills and executive function in DS145. Similarly, in Ts65Dn mice, a positive correlation was recently reported between acquisition of developmental milestones during early postnatal period and cognitive performance in adult life141. The present study showed that prenatal to early postnatal treatment with P021 rescues the delay in some of the motor and sensory developmental milestones.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Individuals with DS present important deficits in cognitive tasks known to depend on the anatomical and functional integrity of the frontal lobe 2 . Importantly, mouse models of DS recapitulate 55 several cognitive deficits of this condition 3,4 .…”
Section: Mainmentioning
confidence: 99%
“…Therefore, dendritic hypotrophy is very likely a second key determinant underlying the poor performance of individuals with DS in many cognitive domains. In addition, the axons of trisomic neurons have a reduced myelination, 7 which implies slower conduction of the action potentials and further impairment in the cross talk among neurons.…”
Section: The Gene Burden Impairs Brain Development In Down Syndromementioning
confidence: 99%